Epidemiology of confirmed measles virus cases, surveillance, incidence, and associated factors in Eritrea: 18-year retrospective analysis - Mengistu, Samuel Tekle; Achila, Oliver Okoth; Tewelde, Asmerom Tesfagiorgis; Hamida, Mohammed Elfatih; Tekle, Freweini; Michae, Issaias; Said, Mensura; Fsahatsion, Dawit; Abai, Haimanot; Mulugeta, Rahel; Tsegai, Tsigehana; Woldu, Luwam Gilazghi; et al. (Frontiers in Public Health, 2023)
Background: Despite the outstanding measles vaccine coverage (MVC) in Eritrea, sporadic outbreaks are not uncommon. In this analysis, we evaluated the incidence and spatiotemporal distribution of measles in Eritrea. An evaluation of the factors associated with measles vaccination and IgM-positive (+) febrile rash was also undertaken. Methods: A retrospective (period: 2002–2020) study was carried out by abstracting data from the integrated disease surveillance and response database (IDSR). Data were analysed using descriptive statistics and binary logistic regression. Spatial variability and distribution of confirmed cases were evaluated using ArcGIS Pro version 3.0.1. Results: In total, 9,111 suspected cases, 2,767(1,431 (51.7%) females) were serologically tested. The median (IQR) age, and minimum-maximum age were 7 years (IQR: 4-14 years) and 1 month-97 years, respectively. Among the 608(21.9%) laboratory-confirmed cases, 534 (87.8%) were unvaccinated and 53 (9.92%) were <1 year old. The crude incidence rate for MV was 14/per 100,000 persons. The age-specific positivity rate per 100,000 suspected cases tested was 21.5 with individuals >30 years presenting with the highest rates (69.9/100,000). Higher odds (OR) of MV test positivity were associated with age at onset – higher in the following age bands (10 – 14 years: OR=1.6 (95%CI: 1.1-2.2, p-value=0.005); 15-29 years: OR=7.0(95%CI: 5.3–9.2, p-value=0.005); and >=30 years: OR=16.7 (95%CI: 11.7-24) p<.001). Other associations included: Address – higher in Anseba (OR=2.3, 95%CI: 1.7-3.1, p-value<0.001); Debub(OR=2.7, 95%CI: 1.9-3.9, p-value<0.001); Gash-Barka(OR=15.4, 95%CI: 10.9-21.7, p-value<0.001); Northern Red Sea (OR=11.8, 95%CI: 8.5-16.2, p-value<0.001); and Southern Red Sea (OR=14.4, 95%CI: 8.2-25.2, p-value<0.001). Further, test positivity was higher in health centers (OR=2.5, 95%CI: 1.9-3.4, p-value<0.001) and hospitals (OR=6.8, 95%CI: 5.1-9.1, p-value<0.001). Additional factors included vaccination status - higher in the unvaccinated (OR=14.7, 95%CI: 11.4-19.1, p-value<0.001); and year of onset of rash (higher >2015: OR=1.4, 95%CI: 1.1-1.7, p-value<0.001). Uptake of measles vaccine associated with a similar complement of factors. Conclusion: In large part, efforts to eliminate measles in Eritrea are hindered by disparities in vaccine coverage, under-surveillance, and low vaccination rates in neighboring countries. Enhanced surveillance and regional micro planning targeting hard-to-reach areas can be an effective strategy to improve measles elimination efforts in Eritrea.